Tackling the Shelter Challenge : Developing the Mortgage Market in Egypt - Nasr, Sahar; Abdelkader, Laila (World Bank, Washington, DC, 2012)
The Egyptian revolution has brought to the forefront the need to focus on job opportunities; transparency and accountability; a fair and competitive environment; as well as equal access to finance, land, and housing-especially for underserved segments of society. Although the government of Egypt embarked on a macroeconomic and structural reform program in 2004, economic and social progress could not keep pace with the aspirations of many Egyptians, and spatial welfare disparities remained unchanged-contributing to the social discontent leading to the revolution. The housing sector tends to be a large part of the economy in most countries. It is a major factor in creating stable societies and a key indicator for social well-being.